1. The problem of political leadership on the example of Yemen - Alexander Gungnin; Marek Delong; Yuliia Lisnevskaya (Przegląd Geopolityczny)
The article analyses the problem of political leadership in developing countries on the example of Yemen. The main source of data for the analysis is the personal experience of one of the authors, who worked for two years in the local higher education system. The activity of Yemen’s national leaders, who headed the authoritarian regime in both parts of the country and who coordinated the political, economic and ideological efforts of the authorities, aimed at modernization of the Arab society, has been chosen as the object of the study. The research focuses on the practice of public administration and social transformations, which was implemented in the Yemen Arab Republic and the National Democratic Republic of Yemen, when Ali Abdullah Saleh (1978-2011) and Ali Nasser Muhammad (1972-1986) - prominent representatives of the modernist authoritarianism, headed these countries. First one was an Arab Marxist, the other a moderate Islamic nationalist. The article uses the method of comparative analysis to show the role and importance of political leadership in Yemen under the conditions of the authoritarian regime. The analysis of relevant leaders’ activities provides serious basis for reflection to managers, political scientists and economists.